2018
DOI: 10.1039/c8cp02924e
|View full text |Cite
|
Sign up to set email alerts
|

Nonstoichiometric oxides as a continuous homologous series: linear free-energy relationship in oxygen exchange

Abstract: A novel methodology for the analysis of oxygen exchange in practically important nonstoichiometric oxides with mixed ionic electronic conductivity (MIEC) is suggested. It is based on the fact that the kinetic and thermodynamic properties of such oxides vary continuously with oxygen stoichiometry. This allows MIEC oxides to be considered as a homologous series, with the difference that traditional series are discrete in their chemical composition whereas MIEC oxides are continuous in oxygen stoichiometry. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Reduction free energies of BaMO 3−δ were calculated here in the manner of Deml et al , and Ezbiri et al Single neutral oxygen vacancies were created by randomly removing one oxygen atom from the 2 × 2 × 2 supercell to afford δ values of 0.125. A number of prior reports have demonstrated that neutral oxygen vacancies, with two trapped electrons, are favored in undoped oxides under reducing conditions. Therefore, this investigation is limited to the formation of neutral oxygen vacancies as the stoichiometry of the perovskite reduction reaction requires the formation of O 2 from two neutral oxygen atoms . Here, the structures of BaMO 3−δ were fully optimized with cubic symmetry and constant volume conditions in the manner of Deml et al and Sundell et al Full details of this method are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction free energies of BaMO 3−δ were calculated here in the manner of Deml et al , and Ezbiri et al Single neutral oxygen vacancies were created by randomly removing one oxygen atom from the 2 × 2 × 2 supercell to afford δ values of 0.125. A number of prior reports have demonstrated that neutral oxygen vacancies, with two trapped electrons, are favored in undoped oxides under reducing conditions. Therefore, this investigation is limited to the formation of neutral oxygen vacancies as the stoichiometry of the perovskite reduction reaction requires the formation of O 2 from two neutral oxygen atoms . Here, the structures of BaMO 3−δ were fully optimized with cubic symmetry and constant volume conditions in the manner of Deml et al and Sundell et al Full details of this method are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…28−31 Therefore, this investigation is limited to the formation of neutral oxygen vacancies as the stoichiometry of the perovskite reduction reaction requires the formation of O 2 from two neutral oxygen atoms. 32 Here, the structures of BaMO 3−δ were fully optimized with cubic symmetry and constant volume conditions in the manner of Deml et al 27 and Sundell et al 24 Full details of this method are provided in the Supporting Information.…”
Section: T H Imentioning
confidence: 99%
“…where the Brønsted coefficient β is redesignated as n and R 0 is the equilibrium exchange rate in the eq 1. 33 A direct consequence of eq 3 is the power-law dependence of R 0 on the equilibrium partial pressure of oxygen pO 2 eq often observed in experiments:…”
Section: Introductionmentioning
confidence: 92%
“…This result is in a good agreement with the literature data, 45,57 in which the change in the Gibbs energy (μO 2 oxide (δ)) in ferrites is almost completely determined by the entropy coefficient, which is caused by the Fe 3+ /Fe 4+ disorder in the oxide lattice. At the same time, in the cobaltites considered in detail in the papers, 24,28,29,33 the dependences of the activation enthalpy R 0 on δ are completely determined by the component of the partial molar enthalpy in μO 2 oxide (δ). It should be understood that in the formal definition of the effective Gibbs activation energy R 0 , defined as −RT ln R 0 , there are summands having an effective entropic form arising due to constant coefficients in R 0 .…”
Section: Analysis Of Linear Energymentioning
confidence: 99%
See 1 more Smart Citation